PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN LKS AUTOPART PADA PT MITRA ABADI AUTOPART DI JAKARTA UTARA - Putra Andhika Toti; Anisa Arizona Bandi (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study aims to determine the effect of price and product quality on purchasing decisions of LKS Autopart at PT. Mitra Abadi Autopart in North Jakarta. The method used is a quantitative method. The population used in this study were visitors to PT. Mitra Abadi Autopart, which has purchased LKS Autopart at PT. Autopart Eternal Partners. The technique used is non-probability sampling with a purposive sampling approach by distributing questionnaires. The data analysis techniques in this study were instrument testing, descriptive analysis, classical assumption testing and hypothesis testing. The results of this study indicate that the price variable (X1) partially has a positive and significant effect on the Purchase Decision (Y) of LKS Autopart at PT Mitra Abadi Autopart North Jakarta by 33.6%. Partially Product Quality (X2) has a positive and significant effect on Purchase Decision (Y) LKS Autopart at PT Mitra Abadi Autopart North Jakarta by 73%. Taken together Price (X1) and Product Quality (X2) have a positive and significant effect on Purchase. Decision (Y) LKS Autopart at PT Mitra Abadi Autopart North Jakarta by 73% and the remaining 27% is influenced by other variables not examined.